Ecotourism Pillars Enforcement to Geotourism Destination in Slamet and Serayu Mountainous Areas, Central Java Province - Mafut Munajat; Ricky Avenzora; Dudung Darusman; Sambas Basuni (Institut Pertanian Bogor (IPB University), 2022)
Nature based tourism, including geotourism, can have the status of ecotourism if they are able to enforce the seven pillars namely: 1) the ecological pillar, 2) the economic pillar, 3) the socio-cultural pillar, 4) the satisfaction pillar, 5) experience pillar, 6) memory pillar, and 7) education pillar. This study aims to analyse the perceptions of tourists towards the enforcement of the seven pillars of ecotourism in geotourism destinations. The study was conducted through a survey using a closed-ended questionnaire with a total number of respondents is 400 people. Data analysis was carried out using comparative quantitative and correlation quantitative methods. The results showed that there was still a “gap” between the pillars of sustainable development and the pillars of the basic needs of tourists. The results of the correlation test showed that the elements of the seven pillars of ecotourism had interrelationship each other. It is necessary to modify the form of geotourism implementation by increasing the aspects of guiding/interpreting for tourists and intensifying the involvement of tourists in all tourism activities. The regional approach are also applied to the development of geotourism so that it is more optimal, integrated and efficient in the use of resources.